The Role of Green Tourism Perception, Environmental Concern and Intention of Participation in Green Tourism on Environmentally Responsible Tourism Behavior - Stella Alvianna; Syarif Hidayatullah; Irany Windhyastiti; Umu Khouroh; Irany Windhyastiti (Jurnal Manajemen dan Kewirausahaan, 2022)
The concept of green tourism has been promoted in several countries to reduce carbon emissions resulting from tourism management and hotel operator practices. Thus, environmental development is very important to minimize the environmental impact of declining tourists due to attraction to nature-based destinations. Therefore, structured tourism activities are required, and attractiveness for tourism sustainability assessment of progress is a high priority. Our research model tends to examine and analyze aspects of tourist behavior towards green tourism sustainability and investigate the relevant linkages to see their tourism behavior that is environmentally responsible. The location of this study is in Batu City, with a total sample of 300 people who have visited Batu City. The variables in this study consist of the independent variable (X) there are 2 variables (Green Tourism Perception (GTP) and Environmental Concern (EC)) the variable between the Intention of Participation in Green Tourism (IPGT) (Z) and the dependent variable: Environmentally Responsible Tourism Behavior  (ERTB) (Y) with analysis technique using regression test of 2 models. The results show that: 1) the direct effect of Green Tourism Perception (GTP) on Environmentally Responsible Tourism Behavior (ERTB) was not significant, 2) the direct effect of GTP on ERTB was not significant, 3) the relationship between GTP and ERTB would be significant if mediated by Intention of Participation in Green Tourism (IPGT)